Green IT [ reduce your information system's environmental impact while adding to the bottom line - Velte, Toby J.; Elsenpeter, Robert C. , 1970-; Velte, Anthony T. (McGraw-Hill, 2008)
Publisher's description -- Although you might not think that computers and servers humming away while doing their jobs have much of an impact on the environment, the reality is that they do. And, going green responsibly is a lot harder than it sounds - it can be a daunting endeavor to sift through all the standards and regulations, technologies, and processes that dot the "green landscape." To guide IT professionals through this process, GREEN IT: Reduce Your Information System's Environmental Impact While Adding to the Bottom Line by Toby Velte, Anthony Velte, and Robert Elsenpeter, explains what measures can be taken to lessen any IT department's environmental impact. It provides both the business case for change, along with a detailed implementation plan to ensure IT departments make as little impact on the environment - and the budget - as possible